Tanggung Jawab Perdata Influencer terhadap Endorsement Produk Bermasalah di Media Sosial - Rizki Wahyudi; Agnes Maria Janni Widyawati; Darmawan Tri Budi Utomo; Mieke Anggraeni Dewi; Saryana Saryana (Jurnal Multidisiplin Indonesia, 2026)
Digital marketing through social media has significantly strengthened the role of influencers in shaping consumer purchasing decisions, yet problematic product endorsements frequently raise legal issues concerning civil liability and consumer protection. This study aims to examine the legal basis, forms, and limits of influencer responsibility in digital marketing practices in Indonesia. The research employs a normative legal method using statutory, conceptual, and case approaches. Primary legal materials consist of the Indonesian Civil Code, Consumer Protection Law, Electronic Information and Transactions Law, and regulations governing electronic commerce, while secondary materials include legal literature and relevant scholarly publications. The findings indicate that although Indonesia has not enacted specific legislation governing influencer liability, legal responsibility can be established through provisions on unlawful acts, negligence, contractual obligations, and consumer protection. Influencers may therefore be held civilly liable when they disseminate misleading information, fail to exercise due diligence, or promote illegal or harmful products that result in consumer losses. The study emphasizes the urgent need for comprehensive and specific regulations to strengthen consumer protection, provide greater legal certainty, and ensure accountability in the rapidly growing digital marketing ecosystem in Indonesia.